Capability components of supply chain resilience for readymade garments (RMG) sector in Bangladesh during COVID-19 - Mohammad Ali; Mahbubur Rahman Syed; Guilherme F. Frederico (Modern Supply Chain Research and Applications, 2021)
Purpose: The readymade garments (RMG) industry acts as one of the foremost vital catalysts for financial as well as social advancement of Bangladesh. Due to the harsh impact of COVID-19, RMG sector has been confronting a never-seen-before phenomenon. Since the supply chain has seriously been influenced, concern raises among industry and policymakers on how to support against disturbances resulting from pandemics. Accordingly, this research aims to explore the vulnerability and capability factors of RMG sector in Bangladesh, their relationship and how these variables affect supply chain resilience. Design/methodology/approach: A qualitative research design has been employed. In the first stage, content analysis has been performed. Since COVID-19 is a new experience, newspapers were the source to become acquainted with the vulnerability and capability factors following the guidelines provided by Pettit et al. (2010). In the second stage, in-depth interviews with key informants were conducted to investigate the relationship among the variables and how these factors may influence supply chain resilience. Findings: This study identifies fourteen capability factors and their sub-factors of RMG industry in Bangladesh in order to improve the resilience capacity against the vulnerabilities in the context of COVID-19 pandemic. Research limitations/implications: This research is based on the setting of particular industry in Bangladesh, where respondents are immersed in a unique culture. Special care is required to generalize the results to other segments and phenomena. Practical implications: The framework recognizes the balanced and unbalanced strength with the capability's components and find the relation between capabilities and vulnerabilities within the fashion industry. By creating the resilience network with the four conceivable positions, companies can find themselves with their capability's components and natural vulnerabilities. Originality/value: This study investigates diverse components of capability figure against vulnerabilities to create the supply chain resilience. This paper, moreover, develops with four conceivable positions with their capabilities against existing vulnerabilities which brings timely contribution considering the context of COVID-19.
Keywords: 650; Readymade garments (RMG); Bangladesh; Supply chain; Resilience; Capability; Vulnerability